Nanoparticles target distinct dendritic cell populations according to their size. - Manolova, V; Flace, A; Bauer, M; Schwarz, K; Saudan, P; Bachmann, M (2008)
The efficiency of a vaccine largely depends on the appropriate targeting of the innate immune system, mainly through prolonged delivery of antigens and immunomodulatory substances to professional antigen-presenting cells in the lymphoid environment. Particulate antigens, such as virus-like particles (VLP) induce potent immune responses. However, little is known about the relative importance of direct drainage of free antigen to lymph nodes (LN) versus cellular transport and the impact of particle size on the process. Here, we show that nanoparticles traffic to the draining LN in a size-dependent manner. Whereas large particles (500-2000 nm) were mostly associated with dendritic cells (DC) from the injection site, small (20-200 nm) nanoparticles and VLP (30 nm) were also found in LN-resident DC and macrophages, suggesting free drainage of these particles to the LN. In vivo imaging studies in mice conditionally depleted of DC confirmed the capacity of small but not large particles to drain freely to the LN and demonstrated that DC are strictly required for transport of large particles from the injection site to the LN. These data provide evidence that particle size determines the mechanism of trafficking to the LN and show that only small nanoparticles can specifically target LN-resident cells.